D&I in Engineering Education, past, present, and future: A Country Case Study of Ireland. Issue 13 (2021) - Doyle-Kent, Mary; Watson, Emily
Abstract: In their annual report, "Engineering 2020. A barometer of the profession in Ireland, " Engineers Ireland state that according to their research, skills shortages continue to be a major concern in Ireland. With 91% of engineering leaders listing this as a barrier to growing their workforce, it was predicted that in 2020 more than 5, 000 engineers would be hired. The modern engineering graduate is entering into a working world which is different to previous generations. They need to be able to take on complex technological problems. In addition, the social, environmental, and economic challenges facing them are unprecedented. Engineers suitably trained will play a critical role in reaching the Sustainable Development Goals as set out by the United Nations. In Ireland there is a noticeable absence of women both studying engineering courses, and, working as professional engineers. This research focuses on why this is traditionally the case. In addition, it suggests that modernising engineering education, which is adapted to the modern working environment, could be instrumental in attracting a more diverse cohort of students in the future.